Business Development of The Ecotourism of Javan Gibbon: A Marketing Mix Strategy at Gede Pangrango National Park - Fandawa Saputra; Tutut Sunarminto; Harnios Arief; Khairiyah Kamilah (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Javan gibbons are a protected species facing conservation challenges in Bodogol Resort, Gunung Gede Pangrango National Park. Ecotourism has been shown to benefit both conservation and local economies in other regions.Purpose: This study aimed to assess visitor perceptions of Javan gibbon ecotourism development using a 4Ps marketing mix approach to identify areas for improvement and inform future conservation and tourism initiatives. The areas for improvement include product attributes such as offered package for tourists, chosen tourist provider, the offered price by seeing the willingness to pay, spots to enjoy the tourism, and effective promotion channels.Methods: Descriptive analysis and statistic descriptive analysis were employed to examine visitor perceptions. Data were collected through surveys administered to visitors to Bodogol Resort.Results: Findings indicate that tourists have a positive perception of Javan gibbon ecotourism, proven by the score given by local tourist and foreign tourists are 5.7 and 5.9 in a row. These scores show the degree of agreement (out of 7) about Javan gibbon ecotourism that brings positive impacts for the environment, social, and the Javan gibbon itself. However, there is a need to enhance the 4Ps marketing mix, including pricing, product offerings, promotion, and place. Specifically, prices should be adjusted based on visitor willingness to pay is IDR500,000 to IDR1,000,000 which have not been analyzed before. Social media promotion should be done with the involvement of influencers and community.Conclusion: This study provides valuable insights into the potential of Javan gibbon ecotourism to contribute to both conservation and local development. By implementing recommended strategies with 4P’s marketing mix approach, Bodogol Resort can further enhance visitor experiences such as formed package to offer to the tourist from various potential activity found from this research. The offered package adjusted to the willingness to pay of local and foreign tourist that ranged from IDR500,000 to IDR1,000,000. Respondents also agree that this ecotourism activity also support the long-term survival of this endangered species.Originality: There’s no business development for javan gibbon ecotourism before at Gunung Gede Pangrango National Park. This research also uses VALS Survey analysis to form the promotion strategy. Keywords: business development, ecotourism, javan gibbon, marketing mix, touris